Coagulation and fibrinolysis in individuals with advanced liver disease - David H. Van THIEL; Magdalene GEORGE; Ayşe L. MINDIKOĞLU; Mehdi H. BALUCH; Sonu DHILLON (Turkish Journal of Gastroenterology, 2019)
-